2022
DOI: 10.1108/ijshe-01-2022-0018
|View full text |Cite
|
Sign up to set email alerts
|

Transforming students’ behaviour preferences: achievable changes by a sustainability course

Abstract: Purpose The purpose of this paper is to examine the impacts of a sustainability course that was designed to evoke measurable transformational changes in students’ preferences and in their roles as consumers, employees and citizens, via consciously addressing sustainability issues and involving a community partner. Design/methodology/approach The research was undertaken using mixed methods. Q-methodology helped create student groups with similar preferences for sustainable attitudes and behaviours before and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Therefore, to draw in voters, a brand must cultivate a positive selfimage that will eventually translate into actual behavior represented in the form of votes. As a result, it can be claimed that a positive attitude is essential to convert a prospective customer into an actual customer [9,42,87,108].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, to draw in voters, a brand must cultivate a positive selfimage that will eventually translate into actual behavior represented in the form of votes. As a result, it can be claimed that a positive attitude is essential to convert a prospective customer into an actual customer [9,42,87,108].…”
Section: Discussionmentioning
confidence: 99%
“…TL and DT look to foster mindset change. To make our societies more sustainable, ESD must take a holistic approach that considers people's entire mindset and encourages consistent behaviour and preference patterns [72]. Mindsets affect cognitive, motivational, and emotional processes and how people act in certain situations [73].…”
Section: Mindset Transformationmentioning
confidence: 99%
“…Prior studies have referred to the importance of engaging consumers in sustainability issues so they can adopt a more sustainable lifestyle [11,29]. Behaving according to sustainability principles starts with having a base knowledge of environmental issues [71]. The study respondents indicated that Saudi society has some knowledge about sustainability issues, but when it comes to sustainable and green purchases, eco-friendly products are not always available, and hence continuous sustainable purchases are mostly challenging.…”
Section: Gen Z's Sustainable Purchasing Behaviormentioning
confidence: 99%